Textological-Philological Study on Arabic Language Sciences in Minangkabau Manuscripts - Akhyar Hanif; Septika Rudiamon (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This paper investigated the types of Arabic linguistics (or Ulûm al-Lughah al-Arabiya) contained in Minangkabau manuscripts and analyzed them according to the context in which the manuscript was found. In addition, this paper also presented text transliteration as a form of Philology work. Furthermore, the research method used was the philology research method by conducting an inventory of manuscripts, description, transliteration, and translation of manuscripts, and finally, analyzing the content of the manuscript and relating it to the social context of the community. This study found one manuscript related to the science of Arabic, namely ‘Ilm al-Nahw which was found in Minangkabau, precisely in the Lunang village, Pesisir Selatan. The manuscript was coded (08/LNG.II/nhw/2019), while the form of text editing was in the form of transliteration and translation. The reason why the manuscript of ‘Ilm al-Nahw was in Lunang Pesisir Selatan and was a collection of the Mande Rubiah museum, was because it was closely related to the main purpose of learning 'Ilm al-Nahw itself in the past in Nusantara, especially in Minangkabau. That was as a tool for teaching and learning, such as to help learning the religious sciences, such as the science of Fiqh, Tawhid, Tafsir, Hadith, and so on, which are indeed mostly written in Arabic. Therefore, to understand them properly requires the science of tools, namely 'ilm al-Nahw